Data Stewardship Research Trends in Organizations - Loso Judijanto (Westscience Press, 2026)
Data stewardship has become an increasingly important research area as organizations recognize data as a strategic asset requiring effective governance, quality management, and responsible utilization. This study aims to examine the development, intellectual structure, and emerging trends of data stewardship research in organizational contexts through a bibliometric analysis approach. Data were collected from the Scopus database using relevant keywords related to data stewardship and organizations, followed by performance analysis and science mapping using VOSviewer. The findings reveal that data stewardship research is strongly influenced by foundational studies on the FAIR (Findable, Accessible, Interoperable, and Reusable) principles, data governance, and research data management. Keyword analysis indicates that data stewardship is closely associated with data management, metadata, data quality, information management, data sharing, privacy, and artificial intelligence. The temporal analysis shows a shift from traditional data management practices toward broader organizational capabilities involving ethical data governance, responsible data sharing, and digital transformation. Collaboration analysis demonstrates that research contributions are concentrated in leading countries and institutions, particularly in the United States and healthcare-related research environments, while international collaboration continues to expand. This study contributes by providing a comprehensive overview of the intellectual development of data stewardship research and identifying future opportunities for integrating governance, technology, and organizational capability perspectives.